Image Noise Suppression Using Color Morphological Filter - Samia Shamaon Lazar (College of Education for Pure Sciences, 2010)
Abstract Morphological filtering is a useful technique for processing and analyzing binary and grayscale images. These filters are effective in impulsive noise filtering, feature extracting, and images enhancing. So it is important to find out method for applying morphological technique on color image and keep the colors unchanged at the same time. This paper deals with the use of morphological filters for suppression "salt & pepper" noise in color images. We have used "component-wise approach", in which grayscale morphological operations are applied to each of the three colors image components independently. We present experimental results of applying this approach for the application of noise suppression in color images.